Effectiveness of herbicides application on soybean - Kyrychok, M.; Remeniuk , S. (Quarantine and plant protection, 2022)
Goal. To establish the effectiveness of the use of herbicides against weeds in soybean crops. Methods. Field and laboratory. Results. The main technologies for growing soybeans are based on the application of soil herbicides after sowing but before the appearance of crop seedlings. The main task of the research was to study the effectiveness of soil action and post-emergence herbicides on the destruction of weeds in soybean crops during the growing season. Establishing the specifics of the application of post-emergence herbicides makes it possible to reliably protect soybeans in case of impossibility or ineffective application of soil herbicides. Separate application of herbicides in smaller doses was used: Nabob, s.c. (bentazone, 480 g/l) 1.0 l/ha on the 4th day after sowing + 1.2 l/ha in the phase of 1—2 soybean leaves; Pari, s.c. (ima-zetapyr, 100 g/l) 0.3 l/ha on the 4th day after sowing + 0.4 l/ha in the phase of 1—2 soybean leaves; Pulsar 40, s.c. (imazamox, 40 g/l) 0.3 l/ha + 0.4 l/ha in the phase of 1—2 soybean leaves; Fabian, w.g. (imazethapyr, 450 g/kg + chlorimuron-ethyl, 150 g/kg) 0.03 kg/ha on the 4th day after sowing + 0.04 kg/ha in the phase of 1—2 soybean leaves; Harmony 75, w.g., (thifensu-lfuron-methyl, 750 g/kg) 0.003 kg/ha + surfactant Trend, 0.2 l/ha twice — after sowing on the 4th day and in the phase of 1—2 soybean leaves. Conclusions. The effectiveness of the imadazoline group of herbicides with split application, where the active substance acts both through the leaves and through the root system of weeds, was lower on average by 11%, than with single application. On average, during the years of research, for the application of the herbicide Pari in the phase of 1—2 soybean leaves, s.c. (1.0 l/ha) destroyed 89.0% of weed seedlings, and with separate application at lower rates (0.3 l/ha on the 4th day after sowing and 0.4 l/ha in phase 1—2 soybean leaves) 78.3% of weeds died. Similarly, for the introduction of Fabian herbicide in phase 1—2 soybean leaves, w.g. (0.1 kg/ha) the efficiency of using the full rate of the drug was 83.8%, and with separate application (0.03 kg/ha on the 4th day after sowing + 0.04 kg/ha in the phase of 1—2 leaves) soybean weed destruction was 72.6%. The use of herbicides with a contact action showed a better efficiency of action with a two-time application. After applying the full dose of the drug Nabob, s.c. (3.0 l/ha) once reduced the number of weeds by 68.7%, and with two applications (1.0 l/ ha on the 4th day after sowing + 1.2 l/ ha in phase 1—2 soybean leaves) the effectiveness of the drug was 83.0%. For Harmony, w.g. with a one-time application of the full rate of the drug, it's overall effectiveness was 67.6%, and when using 3.0 g/ha on the 4th day after sowing and 3.0 g/ ha + 0.2 l/ha of surfactant Trend in phase 1—2 leaves of soybeans — 80.4%.